2006
DOI: 10.5380/rf.v36i1.5596
|View full text |Cite
|
Sign up to set email alerts
|

Produção De Serapilheira Em Diferentes Seres Sucessionais Da Floresta Estacional Semidecidual No Oeste Do Paraná

Abstract: ResumoA vegetação ao longo das margens de um reservatório de hidrelétrica foi classificada em cinco seres sucessionais (fase inicial de sucessão -campo -, capoeirinha, capoeira, capoeirão e floresta secundária). As árvores e arbustos de cada sere foram amostrados em 4 parcelas de 10 x 20 m, e a produção de serapilheira foi estimada com o uso de 12 coletores por sere (4,0 m 2 ). A quantidade de serapilheira depositada aumentou com o avanço da sucessão (9,5 a 11,7 Mg.ha -1 ), embora não tenham sido observadas di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
2
9
2
2
Order By: Relevance
“…The results of this study do not corroborate other studies, which observed that the production of the leaf fraction decreased with the advance of the successional phase in tropical forests (PEZZATO;WISNIEWSKI, 2006;ROCHA, 2006;KÖHLER et al, 2008). Investigating the litterfall in different successional stages of a Subtropical Forest in Paraná, Dickow et al (2012) found a higher leaf deposition in initial stages of succession in relation to the medium and advanced stages of natural regeneration.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study do not corroborate other studies, which observed that the production of the leaf fraction decreased with the advance of the successional phase in tropical forests (PEZZATO;WISNIEWSKI, 2006;ROCHA, 2006;KÖHLER et al, 2008). Investigating the litterfall in different successional stages of a Subtropical Forest in Paraná, Dickow et al (2012) found a higher leaf deposition in initial stages of succession in relation to the medium and advanced stages of natural regeneration.…”
Section: Discussioncontrasting
confidence: 99%
“…Essa porcentagem, normalmente situa-se acima dos 60-70% (CUEVAS; MEDINA, 1986;CUNHA et al, 1993;CUSTÓDIO FILHO et al, 1996;LUIZÃO;SCHUBART, 1986;MACHADO et al, 2008;MARTIUS et al, 2004;MORAES et al, 1999;MARQUES, 2003;ROCHA, 2006;SCHEER, 2006;SILVA et al, 2009;VARJABEDIAN;PAGANO, 1988;VOGEL et al, 2007). A diminuição na porcentagem de folhas (de 77 para 68%), com o avanço da fase sucessional, já foi observada por outros autores em florestas tropicais secundárias em diferentes fases de sucessão (CUNHA, 1997;KÖHLER et al, 2008;PEZZATO;WISNIEWSKI, 2006;MARQUES, 2003;ROCHA, 2006;TOLEDO et al, 2002) e pode estar associada a uma maior produção de serapilheira foliar pelas espécies pioneiras presentes nas fl orestas secundárias em processo inicial de regeneração (MARTINS; RODRIGUES, 1999). Luizão e Schubart (1986), investigando a produção de serapilheira em fl oresta de terra fi rme da Amazônia Central, encontraram maior porcentagem de folhas na capoeira jovem em relação às fl orestas originais de platô e baixio.…”
Section: Resultsunclassified
“…A comparação desses resultados com outros encontrados na literatura torna-se complexa, em razão de uma grande variação natural na deposição dessas frações e às formas de amostragem e triagem utilizadas. Alguns autores computaram os pesos dos ramos juntamente com os órgãos reprodutivos (PINTO; MARQUES, 2003;ROCHA, 2006), outros separaram os órgãos reprodutivos em fração fl ores e fração frutos (TOLEDO et al, 2002), outros triaram a serapilheira somente em duas frações, foliar e lenhosa (GAMA-RODRIGUES; BARROS, 2002;LUIZÃO;SCHUBART, 1986;WERNECK et al, 2001) ou, ainda, não fi zeram distinção entre os elementos reprodutivos e a miscelânea (CUSTÓDIO FILHO et al, 1996;FIGUEIREDO FILHO et al, 2003;KÖNIG et al, 2002;LEITÃO FILHO, 1993;MORELLATO, 1992;PAGANO, 1989;PEZZATO;WISNIEWSKI, 2006;PINTO et al, 2008;SILVA, 1984). Diante do exposto, as comparações devem ser cautelosas, levando-se em conta essas possíveis variações.…”
Section: Dickow K M C Et Alunclassified
“…Thus, it is possible that this community responded more efficiently to local water conditions, showing that soil water deficit might trigger a defense mechanism of trees against a possible situation of water stress, thus promoting the fall of leaves as a strategy of economy in the use of water, even if this costs a smaller carbon assimilation through photosynthesis. This might also be a response triggered by hormonal mechanisms (PEZZATTO; WISNIEWSKI, 2006), in which the sensitivity by the lack of water in the soil may trigger physiological, morphological and structural changes. Other papers also reported this water-saving strategy for plant community, as reported in the work de Menezes et al (2010) and Sanches et al (2009).…”
Section: Discussionmentioning
confidence: 99%